"Sharenting, " parent blogging, and the boundaries of the digital self. (3rd April 2017) - Blum-Ross, Alicia; Livingstone, Sonia
ABSTRACT: This article asks whether "sharenting" (sharing representations of one's parenting or children online) is a form of digital self-representation. Drawing on interviews with 17 parent bloggers, we explore how parents define the borders of their digital selves and justify what is their "story to tell." We find that bloggers grapple with profound ethical dilemmas, as representing their identities as parents inevitably makes public aspects of their children's lives, introducing risks that they are, paradoxically, responsible for safeguarding against. Parents thus evaluate what to share by juggling multiple obligations—to themselves, their children in the present and imagined into the future, and to their physical and virtual communities. The digital practices of representing the relational self are impeded more than eased by the individualistic notion of identity instantiated by digital platforms, thereby intensifying the ambivalence of both parents and the wider society in judging emerging genres of blogging the self.